Knowledge of naloxone and take-home naloxone programs among a sample of people who inject drugs in Australia: Variations across capital cities - Dietze, P.; Stare, M.; Cogger, S.; Nambiar, D.; Olsen, A.; Burns, L.; Lenton, Simon (Wiley-Blackwell Publishing Ltd., 2018)
© 2017 Australasian Professional Society on Alcohol and other Drugs (APSAD). Introduction and Aims: Take-home naloxone (THN) programs targeting people who inject drugs (PWID) have been running in some Australian states and territories since 2012. In this study, we aimed to determine the extent to which PWID in the capital cities of all Australian states and territories are aware of naloxone and THN programs, whether awareness of these programs has changed over time. Design and Methods: Data were obtained from cross-sectional surveys of a total of 2088 PWID conducted annually as part of the Illicit Drug Reporting System from 2013 to 2015. Specific questions about THN added to the survey in 2013 allowed assessment of the extent to which sampled PWID were aware of naloxone and its function and THN programs in Australia and whether they had participated in a THN program. These main outcomes were examined over time and across states and territories using a mix of descriptive statistics and logistic regression. Results: Over 80% of the sample reported having heard of naloxone across survey years. Less than half of the participants reported having heard of THN programs in 2013 (35%), but this increased to just over (52%) half in 2015 (P < 0.01). Changes over time differed across cities with increases in reports of having heard of THN occurring over time most clearly in those cities with operational THN programs. Discussion and Conclusions: Around half of the PWID sampled for this study are aware of THN programs. Further work is needed to ensure widespread awareness of THN programs which should include implementing THN in all Australian states and territories.